The relevance of the value relevance literature for financial accounting standard setting: another view - Barth, Mary E; Beaver, William H; Landsman, Wayne R (Journal of Accounting and Economics, 2001)
This paper explains that value relevance research assesses how well accounting amounts reflect information used by equity investors, and provides insights into questions of interest to standard setters. A primary focus of financial statements is equity investment. Other uses of financial statement information, such as contracting, do not diminish the importance of value relevance research. Value relevance questions can be addressed using extant valuation models. Value relevance studies address econometric issues that otherwise could limit inferences, and can accommodate and be used to study the implications of accounting conservatism.